2021
DOI: 10.3390/su13105535
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Corporate Governance Index on Financial Performance in the Romanian and Italian Banking Systems

Abstract: Background: Our study aims to verify the impact of corporate governance index on financial performance, namely return on assets (ROA), general liquidity, capital adequacy and size of company expressed as total assets in the banking sector for both a developing and a developed country. In addition, we investigate the interactive effect of corporate governance on a homogenous and a heterogeneous banking system. These two banking systems were chosen in order to assess the impact of corporate governance on two dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…The relationship between a financial institution performance and corporate governance was debated during the time by the authors such as Benvenuto et In the Romanian context, Benvenuto et al (2021) assessed the impact of the corporate governance index on the financial performance in the Romanian and Italian banking systems for the period 2007-2018. For Romania, the authors identified that the effective implementation of corporate governance within the banking system had a positive long-term impact on profitability.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between a financial institution performance and corporate governance was debated during the time by the authors such as Benvenuto et In the Romanian context, Benvenuto et al (2021) assessed the impact of the corporate governance index on the financial performance in the Romanian and Italian banking systems for the period 2007-2018. For Romania, the authors identified that the effective implementation of corporate governance within the banking system had a positive long-term impact on profitability.…”
Section: Introductionmentioning
confidence: 99%
“…Control variables are included in regression analyses to estimate the causal effect of a treatment on an outcome. To study the impact of independent variable on dependent variables in multiple regression total assets of the selected banks have been taken as control variable as a measure of firm size (Dang, Li, & Yang, 2018), (Basuony, Mohamed, & Al-Baidhani, 2014), (Benvenuto, Avram, Avram, & Viola , 2021). The log transformation can be used to make highly skewed distributions less skewed.…”
Section: Methodsmentioning
confidence: 99%
“…Corporate governance reconciliation studies offer a wide range of qualitative and quantitative analyzes that reveal the degree, scope, and levels of compliance (Seidl 2013; Shrivers and Niamh 2015; and Okhmatovskiy 2017), in addition to its importance to the bank's performance and value (Stiglbauer and Velte 2014; Rose 2016; Roy and Pay 2017). Besides this, the most recent study in the field of CG, performed by Benvenuto et al (2021), analyzes the influence of CG in Romania and Italy, using financial indicators also CG components in productivity and shareholder value protection turns out to be significant in both cases. This study's sample included 34 Romanian banks as well as over 350 Italian banks that used the dynamic VAR techniques, which were integrated at various levels.…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…𝛽 ′ = 𝛽 0 𝛽 1 𝛽 3,…, 𝛽 𝑡+,𝑛 ……………………………………………………………………………………....………... (5) Our specific scenario's formula is derived from this formula, and it looks like this: LAssests i,t = α + β 1 NIM i,t + γ 2 NIM i,t + β 3 NPL′s i,t + γ 4 NPL′s i,t + β 5 ELR i,t + γ 6 ELR i,t + β 7 SB i,t + γ 8 SB i,t + β 9 CSM i,t + γ 10 CSM i,t + β 11 CSF i,t + γ 12 CSF i,t + β 13 SBC i,t + γ 14 SBC 15 +  it ………………………………………………………………………………….…….. (6) Econometric Findings Empirical analysis requires flow logic before commenting on the results, applying some diagnostic tests on the appropriateness of the applied approach. Therefore, the diagnostics of the approach was initially done through R 2 , wherein our case is 63.7 percent of the independent variables explain the dependent variables, also for multicollinearity testing was applied VIF, where the mean value of the variables is 9.62 which proves that the data do not have multicollinearity problem.…”
Section: …………………………………………………………………………………………………… (4)mentioning
confidence: 99%
See 1 more Smart Citation